A Gambaran Persepsi Masyarakat Terhadap Vaksinasi Covid-19 Di Wilayah Kerja Puskesmas Harapan Raya - Muhammad Anhsari Halilintar; Susi Erianti; Siska Mayang Sari (STIKes Payung Negeri Pekanbaru, 2022)
Abstract The COVID-19 pandemic has threatened the health of human life, especially in the Pekanbaru City, so the vaccination program is the last resort, and is still being carried out in an effort to overcome it. The existence of a stimulus to the COVID-19 vaccination, giving rise to various behavioral responses and public perceptions, both positive and negative perceptions. The purpose of this research to describe the public perception of the COVID-19 vaccine in the Work Area Harapan Raya’s Health Center. The research method is quantitative with a descriptive design, for the sampling technique using accidental on 172 respondents with a questionnaire instrument. Data analysis was univariate in this studied. The results showed that 87 respondents (50.6%), more dominantly had negative perceptions, with various reasons and respondents' level of doubt, (51.2%) respondents still doubted that inactivated vaccines had a severe reaction compared to other types of vaccines, (43.0%) of respondents answered that vaccines cannot fight more than one virus, and (37.8%) of respondents doubted that the COVID-19 vaccine protects a person in the long term. (37.2%) of respondents stated that vaccine doubts outweighed the risks of not choosing to be vaccinated against COVID-19. This indicates that the public must be more active in sorting out good information, with education from the government related to COVID-19 vaccination.